Note from the Editors. Issue 1 (6th May 2014) - Hansson, Gunnar Ólafur; Miestamo, Matti; Ringen, Catherine; Vikner, Sten; Westergaard, Marit
<x content-type="archive" xml:space="preserve">Abstract</x> This is the first issue of volume 37 of the Nordic Journal of Linguistics. NJL is the journal of the Nordic Association of Linguists. Individuals may subscribe to the Journal by joining the Nordic Association of Linguists. The NAL membership form can be found on the Cambridge University Press web site of NJL, http://journals.cambridge.org/NJL, as well as on the NAL web site, http://www.uef.fi/nal.